Penerapan Metode Tahfizh Al-Qur'an dalam Mencapai Target Hafalan di Madrasah Ibtidaiyah Terpadu Tahfizhul Qur'an Al-Ma'shum (MITTQUM) Surakarta - Hamdani, Arfan; Subando, Joko (TSAQOFAH, 2026)
Tahfizh Al-Qur’an programs in madrasah ibtidaiyah require the application of appropriate methods to ensure that students’ memorization targets are achieved optimally. This study aimed to describe the implementation of tahfizh Al-Qur’an methods and the attainment of students’ memorization targets in the tahfizh program class at Madrasah Ibtidaiyah Terpadu Tahfizhul Qur’an Al-Ma’shum Surakarta. The study employed a qualitative approach, with data collected through observation, interviews, and documentation. The findings show that the tahfizh methods implemented included talaqqi, tikrār, ziyādah, murāja‘ah, and tasmi‘, which were carried out in a structured and integrated manner and thus played an important role in shaping students’ recitation accuracy, fluency, and memorization stability. The attainment of memorization targets was influenced by internal factors, such as students’ motivation, discipline, and cognitive abilities, as well as external factors, including teacher competence, a conducive learning environment, and parental support. Accordingly, the success of a tahfizh program requires synergy between the use of appropriate instructional methods, optimal teacher roles, and sustained collaboration between schools and families in supporting the Qur’an memorization process.